1985
DOI: 10.1002/oms.1210201104
|View full text |Cite
|
Sign up to set email alerts
|

Stable [C2H7O2]+ isomers: Experimental and theoretical evidence for the existence of protonated peroxides and proton‐bound dimers in the gas phase

Abstract: Evidence is presented for the gas phase generation of at least eight stable isomeric [ CH,0CHz6Hz (c)). The important points of the present study are (i) that these ions are prevented by high barriers from facile interconversion and (ii) that both electron-impact-and proton-induced gas phase decompositions seem to proceed via multistep reactions, some of which eventually result in the formation of proton-bound h e r s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“… a (i) from ref , (ii) from ref and , (iii) from ref −32, (iv) from ref . b Energies calculated at level A , but with the thermal energy corrections obtained from frequency analyses 14 using the RHF/6-31G* basis set. …”
Section: Resultsmentioning
confidence: 99%
“… a (i) from ref , (ii) from ref and , (iii) from ref −32, (iv) from ref . b Energies calculated at level A , but with the thermal energy corrections obtained from frequency analyses 14 using the RHF/6-31G* basis set. …”
Section: Resultsmentioning
confidence: 99%
“…Its strength is, however, limited by steric and electrostatic constraints, as attested by a nonlinear O–H$\cdots $ O arrangement. According to a FAB study, protonation of ethylene glycol gives rise to an ion of the type ${\rm HO(CH}_{{\rm 2}} {\rm )}_{{\rm 2}} {\rm OH}_{{\rm 2}}^{{\rm + }} $ (Van Driel et al, 1985). …”
Section: Alcohols and Ethersmentioning
confidence: 99%
“…The proton affinity of ethyl hydroperoxide has not been experimentally determined, but its protonation sites have been studied theoretically. HF/3‐21G calculations have shown that protonation of the internal oxygen is favored by 15 kJ/mol (Van Driel et al, 1985). Our G3 calculations lead to a value of 27 kJ/mol and a proton affinity of 749 kJ/mol, and underline the greater stabilization effect of the ethyl group compared to the methyl group.…”
Section: Alcohols and Ethersmentioning
confidence: 99%
See 2 more Smart Citations